Quantitative evaluation of solar wind time‐shifting methods. Issue 11 (5th November 2016) - Cameron, Taylor; Jackel, Brian
Abstract: Nine years of solar wind dynamic pressure and geosynchronous magnetic field data are used for a large‐scale statistical comparison of uncertainties associated with several different algorithms for propagating solar wind measurements. The MVAB‐0 scheme is best overall, performing on average a minute more accurately than a flat time‐shift. We also evaluate the accuracy of these time‐shifting methods as a function of solar wind magnetic field orientation. We find that all time‐shifting algorithms perform significantly worse (>5 min) due to geometric effects when the solar wind magnetic field is radial (parallel or antiparallel to the Earth‐Sun line). Finally, we present an empirical scheme that performs almost as well as MVAB‐0 on average and as well as MVAB‐0 for intervals with nonradialB . Key Points: We show that solar wind time‐shifting technique accuracy depends greatly on IMF azimuth We provide numerical uncertainties for solar wind time‐shifting methods derived from a large‐scale statistical analysis We introduce a new time‐shifting method that is much simpler than other methods while performing almost well as the best performing method